Re-writing the domestic role: transnational migrants’ households between informal and formal social protection in Ecuador and in Spain - Castellani, S. (2019)
Ecuadorian migration to Spain can be described as an emblematic case of feminization of international migration. As the scholarship showed, this migration flow has been shaped by transnational female social networks in which different types of capital circulate and which are re-produced across generations, providing social protection for people involved in them, both migrants and non-migrants. Starting from three ethnographic studies conducted with Ecuadorian adults and teenage migrants in Seville and in different Ecuadorian localities between 2004 and 2011, this paper has two aims. First, it investigates the crucial role played by migrant women of the first and second generation to create a safety net for the members of their transnational households, in terms of child and elderly care, combining tactically both informal and formal social protection along the different stages of their migratory projects. Second, adopting an intersectional lens, which looks particularly at the dialectic between gender and generation, it analyses the tensions and conflicts generated by the re-positioning of these women within their transnational households. The paper contributes to the literature through questioning the changing gender role and relations in transnational social protection.